PENGARUH CITRA MEREK, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA: Studi Kasus Pada Dealer Nasmoco Cilacap - Ariputra, Aditya; Saputro, Irwan; Jayanti , Esih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to analyze the influence of brand image (X1), price (X2), and product quality (X3) on the purchase decision (Y) of Toyota cars at the Nasmoco Cilacap dealership. Data collection was conducted by distributing questionnaires to Toyota car consumers at the Nasmoco Cilacap dealership during the 2019–2025 purchase period. The sampling technique used was simple random sampling with a sample size of 210 respondents. Data analysis methods included validity and reliability tests, the MSI (Method of Successive Interval) test, classical assumption tests (linearity, normality, multicollinearity, and heteroskedasticity), multiple linear regression analysis, and hypothesis testing consisting of t-tests, F-tests, and analysis of the coefficient of determination (R²). The results of the study indicate that brand image and price do not have a significant effect on purchasing decisions, while product quality has a positive and significant effect on purchasing decisions.